American diplomacy - Kennan, George F. (The University of Chicago Press, 2012)
For more than sixty years, George F. Kennan's American Diplomacy has been a standard work on American foreign policy. Drawing on his considerable diplomatic experience and expertise, Kennan offers an overview and critique of the foreign policy of an emerging great power whose claims to rightness often spill over into self-righteousness, whose ambitions conflict with power realities, whose judgmentalism precludes the interests of other states, and whose domestic politics frequently prevent prudent policies and result in overstretch. Keenly aware of the dangers of military intervention and the.